1985
DOI: 10.1042/bj2300481
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of rabbit brain and liver 4-aminobutyrate aminotransferases isolated by monoclonal-antibody immunoadsorbent chromatography

Abstract: The use of a monoclonal-antibody immunoaffinity column for the rapid isolation of 4-aminobutyrate aminotransferases (EC 2.6.1.19) from rabbit brain and liver is described. Homogeneous enzyme protein is eluted from the immunoadsorbent with 100mM-citrate buffer, pH5, and remains stable at 4 degrees C for several days. One such column (bed volume 8 ml) has been used 40 times in a 9-month period to isolate 10-15 units of enzyme activity (specific activity approx. 3.5-7.5 units/mg) per extraction. Kinetic and spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
1
4
0
1
Order By: Relevance
“…2, the enzyme was eluted as a monomer over a narrow pH range, i.e., 5.0-5.2, whereas a dimer is predominantly eluted from the column when the pH of the eluant buffer is above pH 5.8. This result confirms the previous observations of Kirby et al [4], who reported the dissociation of dimeric Gaba-t by decreasing the pH of the medium.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…2, the enzyme was eluted as a monomer over a narrow pH range, i.e., 5.0-5.2, whereas a dimer is predominantly eluted from the column when the pH of the eluant buffer is above pH 5.8. This result confirms the previous observations of Kirby et al [4], who reported the dissociation of dimeric Gaba-t by decreasing the pH of the medium.…”
Section: Resultssupporting
confidence: 93%
“…The rotational correlation time of the pyridoxal-P form of the enzyme determined at neutral pH indicates strong interaction between the protomers even on the nanosecond time scale [3]. However, gel filtration experiments conducted at low pH values indicate that the elution profile of the aminotransferase undergoes remarkable changes at pH 5.0 [4].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…В гепатоцитах были обнаружены полный набор ферментов обмена ГАМК, аналогичный головному мозгу, однако печеночные формы ферментов катаболизма ГАМК являются более неспецифическими [21][22][23]. Так, ГАМК-Т печени способна к переаминированию не только ГАМК, но и b-аланина и пищевых w-аминокислот, а её функции отличаются от функций фермента, локализованного в нервной ткани, поскольку ГАМК не является в печени нейромедиатором [21,22]. Позже было показано, что первично в печени происходит синтез ГАМК-Т, по строению аналогичной ферменту мозгового типа.…”
Section: результаты и обсуждениеunclassified
“…A few data relative to -aminotransamination are available in mammalian tissues (Roberts & Bregoff, 1953) and microorganisms . Especially 7-aminobutyrate transaminase (Churchich, 1982; Yonaha & Toyama, 1980a,b; White & Sato, 1978;Schousboe et al, 1973;Bloch-Tardy et al, 1974;John & Fowler, 1976; Kirby et al, 1985) and /3-alanine transamination (Yonaha & Toyama, 1980b;Yonaha et al, 1983Yonaha et al, , 1985aNishizuka et al, 1959;Hayaishi et al, 1961) have been investigated. -Aminovalerate transamination has been observed in beef brain (Baxter & Roberts, 1958), pig liver (Buzenet et al, 1978), mouse brain (Schousboe et al, 1973), Pseudomonas SP 126 (Yonaha & Toyama, 1980a), and acetone powder of brain, liver, Escherichia coli and Aspergillus fumigatus (Roberts, 1954), but only one -aminovalerate aminotransferase (2.6.1.48) within our knowledge has been partially purified from lysine-adapted cells of Pseudomonas (Ichihara et al, 1960).…”
mentioning
confidence: 99%